Gestión administrativa de la cooperativa flota Babahoyo interprovincial (FBI) - Gómez Leiton, Evelyn Jimabel (2022)
The administrative management in the Babahoyo Interprovincial Flota Cooperative is essential in all work groups with the objective of achieving the goals and obtaining the best results, the employees do not work comfortably because the place is small and therefore the collaborators do not have an order in everything, since this produces the waiting of several Partners and therefore their disagreement. The present case study is viable because the Administrative Management contemplates its four functions such as planning, organization, direction and control and at the moment of applying this administrative process the knowledge of the officials that make up the Babahoyo Interprovincial Fleet Transport Cooperative is deepened. (FBI), so that through this succession the clients who choose this means of transport get the best perspective of it. The objective of this investigation is going to be of enormous importance for the FBI Cooperative, which facilitates the execution of its functionalities for an optimization in the operation and definition to be carried out in the future, thus achieving and proposing defined goals to achieve in the long term. , taking by the hand all the necessary processes in its continuous optimization and that finally manages to represent its reports as another Cooperative using well the articulation of the administrative and management process.